Effects of concentration of NPK fertilizer as a Nitrogen Source in fermentation of Bioethanol - Nur Hajidah Salsabila; Hiero Azi Priawan; Isna Nur Hasanah; Abdul Haris Mulyadi; Mubshair Naveed; Alwani Hamad (Research in Chemical Engineering, 2024)
Bioethanol is a versatile raw material widely used in the production of ethanol derivatives, pharmaceuticals, fuel additives, alcoholic beverages, solvents, and medicines. Its production involves a fermentation process that can be optimized by adjusting nutrient concentrations. This study investigates the effects of NPK fertilizer concentration as a nitrogen source on the yield and density of bioethanol produced from sugarcane fermentation. The concentrations of NPK fertilizer tested were 0.00%, 0.10%, 1.00%, and 2.00%. The results indicate that low concentrations of NPK, particularly 0.10%, significantly enhanced ethanol production, achieving the highest bioethanol yield of 3.71%. This increase in yield is attributed to the essential nutrients provided by NPK, which support microbial growth and fermentation efficiency. However, as NPK concentration increased to 1.00% and 2.00%, ethanol yield sharply declined to 1.24% and 1.20%, respectively, likely due to osmotic stress and the proliferation of non-ethanol-producing microorganisms, which hindered fermentation efficiency. Regarding bioethanol density, no significant differences were observed across the varying NPK concentrations, with values ranging from 2.31 g/mL to 2.33 g/mL, suggesting that nitrogen supplementation does not influence the physical properties of the bioethanol. The density of the bioethanol produced was far higher than the Indonesian National Standard for fuel-grade ethanol, indicating the need for further purification processes, such as distillation or dehydration, to meet quality standards. These findings highlight the importance of optimizing NPK fertilizer concentrations to maximize ethanol yield while emphasizing the role of post-fermentation treatments for improving bioethanol quality